(untitled) (Research, Society and Development, 2020)
Objective: The aim of this study was to determine the profile and prevalence of maxillofacial injury (MFI) and to assess associated factors in women victims of domestic violence. Methodology: This was a cross-sectional and analytical study that evaluated 514 records of women victims of domestic violence diagnosed with MFI attended at a public reference urgency and trauma hospital in Northeastern Brazil. Descriptive and multivariate statistics were performed using Poisson regression. Results: The prevalence of fractures and facial lacerations was 80.2% and 19.8%, respectively, the majority with low severity (92.1%). Associations were observed between MFI severity and alcohol / drug consumption by the perpetrator (PR=0.251; 95%CI=0.106-0.595; p=0.002) and the night shift (PR=4.675; 95%CI= 1.745-12.525; p=0.002). Correlations were found between MFI severity and length of hospital stay (r=0.148; p<0.01). Conclusions: The prevalence of fractures was considered high and MFI severity was associated with longer hospital stay and alcohol / drug consumption by the perpetrator and the night shift. Strategies need to be adopted as improving the quality of health care for users, social investment in women in vulnerability, overt supervision by security agencies, as well as the implementation of educational programs focused on preventing this condition.